2021
DOI: 10.1111/ped.14536
|View full text |Cite
|
Sign up to set email alerts
|

Survey on children with cerebral palsy in Tochigi Prefecture, Japan

Abstract: Background The incidence of cerebral palsy (CP) is influenced by perinatal medicine and regional medical systems. We investigated the recent incidence of CP and the current problems of children with CP in living at home under an advanced perinatal medical system in Tochigi Prefecture, Japan. Methods A clinical datasheet survey was performed among 13 hospitals and six rehabilitation facilities treating children with CP born in Tochigi Prefecture to estimate the incidence of CP among children born between 2009 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The hypotheses put forward for these differences between preterm and term-born children with the same (spastic) forms are notably that of a different cerebral vulnerability [ 32 ] and brain’s ability to compensate better when it is less well developed [ 34 ]. However, some studies have shown inconclusive [ 37 ] or contradictory results [ 25 ]. Other studies focused on children with the same type of brain lesions [ 38 , 39 ] have shown clinical differences between preterm and term born children with a greater severity of motor impairment in preterm children, leading the authors to suggest that "despite a common radiologic pattern, these are different clinicopathologic entities."…”
Section: Discussionmentioning
confidence: 99%
“…The hypotheses put forward for these differences between preterm and term-born children with the same (spastic) forms are notably that of a different cerebral vulnerability [ 32 ] and brain’s ability to compensate better when it is less well developed [ 34 ]. However, some studies have shown inconclusive [ 37 ] or contradictory results [ 25 ]. Other studies focused on children with the same type of brain lesions [ 38 , 39 ] have shown clinical differences between preterm and term born children with a greater severity of motor impairment in preterm children, leading the authors to suggest that "despite a common radiologic pattern, these are different clinicopathologic entities."…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with severe neurological impairment have difficulty feeding [23,24]. Their energy consumption is usually too high, and their intake is deficient.…”
Section: Discussionmentioning
confidence: 99%
“…2 Dysphagia is a common but critical problem in severely impaired motor and intellectual disabilities (SMID). According to a systematic review, in Japan, the prevalence of dysphagia is 28% in children with cerebral palsy 3 and around 50% across the lifespan of cerebral palsy. 4 Dysphagia is classified into oropharyngeal and esophageal dysphagia, according to anatomical site.…”
mentioning
confidence: 99%